Sistem Informasi Geografis Pencarian Layanan Vaksin dan PCR Covid-19 Menggunakan Google Maps API dan Jalur Terpendek - Haromain, Imam; Munir, Sirojul; Wahyudi, Riyan (LPPM STT Terpadu Nurul Fikri, 2022)
The need for information on the location of health services for Covid-19 vaccines, swabs and PCR in the era of the Covid-19 pandemic and pre-pandemic is something that the public is looking for. The ease and speed of getting the location and route of health services can help the community, so that the vaccine program and the enforcement of the Covid-19 diagnosis can run optimally. Geographic Information Systems (GIS) can be applied in the health sector such as spatial-based health service applications. This research is designing a web-based GIS using Google Maps API technology and the shortest path search algorithm. The software development method used is a prototype model and data collection techniques. The system prototype was tested using the blackbox testing method with the results of system testing obtained 100% all functional running well. This research has succeeded in making a prototype of the GIS application to find the nearest health service for vaccines, swabs and PCR Covid-19 as well as recommendations for the total travel costs that must be incurred to the location so that it can help the community, and the application is feasible to use.